SAT0076 Utility of Survivin Measurements for Early Recognition of Clinically Suspect Arthralgia and Diagnosis of Rheumatoid Arthritis in West Sweden. (15th July 2016) - Bokarewa, M.; Turkkila, M.; Bratt, S.; Erlandsson, M.; Pullerits, R.
Abstract : Background: Recognition of rheumatoid arthritis (RA) at preclinical stages is essential for successful treatment, long-term functional ability and survival. Available serological markers of the disease are restricted to acute-phase reactants and presence of autoantibodies - rheumatoid factor (RF) and ACPA. Although specific, these markers cover less than a half of the patients with RA. Oncoprotein survivin has been recently identified as a marker of severe RA frequently associated with progressive joint damage and poor response to antirheumatic treatment (1). A pilot study on the samples from the Nordic Biobank showed that survivin could predict development of RA several months ahead of clinical symptoms (2). Objectives: To validate the utility of survivin measurements for early recognition of clinically suspect arthralgia and diagnosis of RA in the epidemiological setting. Methods: The first-visit patients with joint pain from the inception cohort of 5455 subjects tested for RF and/or ACPA during 12 consecutive months at the Laboratory of Clinical Immunology at the University Hospital of Gothenburg, were evaluated for RA diagnosis by the 2010 EULAR/ACR criteria (3). Patients with known diagnosis of RA, other rheumatic disease and chronic pain conditions were excluded. The subjects not fulfilling RA diagnosis at the first visit were prospectively followed during 29–49 months. The utility of survivin measurement and arthritis-specific autoantibody status (ACPA and/or RF) for RA diagnosis were analyzed. Results: The total of 385 patients were included in the study. RA criteria applied to the records of the first visit identified 17% of patients as RA. Additional 21% of patients were recognized as undifferentiated arthritis (UA), while the remaining 62% of the patients were characterized as arthralgia. Majority of the RA patients were survivin positive (52%) with an overlap for antibodies (RF and/or ACPA) in 88%. The UA and arthralgia groups had low prevalence of patients positive for survivin (p=0.018) and for autoantibodies (p=0.002). During the follow-up period, 23 cases of new RA and 5 new UA were registered. The incidence of new cases was significantly higher among the survivin-positive patients and corresponded to the increased risk compared to survivin-negative (p=0.008). The combination of survivin and autoantibodies increased further the risk for development of the disease compared to negative patients (RR 4.05[ 1.73–9.20], p=0.002). The presence of isolated survivin was also associated with higher risk of RA (RR 2.55 [1.14–5.71], p=0.028), while no increase in RA risk could be shown for the isolated presence of autoantibodies. Conclusions: This prospective study showed in the epidemiological setting that the presence of survivin was associated with an increased risk of RA. Combination of survivin and autoantibodies further increased this risk. References: Svensson B et al. Increased expression of proto-oncogene survivin predicts joint destruction and persistent disease activity in early RA. Ann Med. 2010;42:45–54. Bokarewa M et al. Survivin but not Flt3 ligand is up-regulated before the onset of RA: a pilot study. Arthritis Res Ther. 2014;16:R45. Cader MZ et al. Ann Rheum Dis. 2011;70:949–55. Disclosure of Interest: None declared